A narrative synthesis of research evidence for tinnitus-related complaints as reported by patients and their significant others - Hall, Deborah A.; Fackrell, Kathryn L.; Li, Anne Beatrice; Thavayogan, Rachel; Smith, Sandra; Kennedy, Veronica; Tinoco, Catarina; Rodrigues, Evalina D.; Campelo, Paula; Martins, Tânia D.; Martins Lourenço, Vera; Ribeiro, Diogo; et al. (BioMed Central, 2018)
Background: There are a large number of assessment tools for tinnitus, with little consensus on what it is important to measure and no preference for a minimum reporting standard. The item content of tinnitus assessment tools should seek to capture relevant impacts of tinnitus on everyday life, but no-one has yet synthesised information about the range of tinnitus complaints. This review is thus the first comprehensive and authoritative collection and synthesis of what adults with tinnitus and their significant others report as problems in their everyday lives caused by tinnitus.